The Archaeology of Elam : Formation and Transformation of an Ancient Iranian State. - Potts, D. T. (Cambridge world archaeology., 1999)
Few major peoples of the ancient Near East have been as little studied as the Elamites, despite their impact from c. 2600 BC to the first centuries AD. This first synthesis in English of Elamite archaeology in over fifteen years will be a major resource for scholars and students.